2020
DOI: 10.1038/s41598-020-66509-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-different extent of resection for clinical IA non-small cell lung cancer: analysis of nodal metastasis

Abstract: Whether age has any impact on the risk of lymph node (LN) metastasis in patients with early-stage non-small cell lung cancer (NSCLC) remains controversial. Therefore, we aimed to objectively compare the risk of LN metastasis between elderly and young patients so as to justify for age-different extent of surgical resection for treating these patients. We retrospectively collected clinical data of patients undergoing lobectomy or segmentectomy with systematic hilar and mediastinal LN dissection for clinical stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…The underlying mechanism that the effect of number of lymph nodes on long-term survival diminishes with age is currently unclear. Considering the equivalent NCSS between the two age groups, our study resonated with the results obtained by Han-Yu Deng et al (38) that age could be an independent predictor of lymph node metastasis, which indirectly affected the oncological effects of lymph node harvesting in elderly patients. This question is expected to be solved in more extensive and specific research in the future.…”
Section: Discussionsupporting
confidence: 88%
“…The underlying mechanism that the effect of number of lymph nodes on long-term survival diminishes with age is currently unclear. Considering the equivalent NCSS between the two age groups, our study resonated with the results obtained by Han-Yu Deng et al (38) that age could be an independent predictor of lymph node metastasis, which indirectly affected the oncological effects of lymph node harvesting in elderly patients. This question is expected to be solved in more extensive and specific research in the future.…”
Section: Discussionsupporting
confidence: 88%
“…The superior outcome of the lobectomy cohort in the smaller tumor group could also be explained by a greater proportion of wedge resections being performed for those tumors <2 cm, and more segmentectomies for those tumors >2 cm resulting in oncologic outcomes approximating lobectomy. Furthermore, we could not conclude the favorable surgical approach in the elderly patients regarding long-term survival, which was in line with prior research (26), and might be attributed to a low malignant behavior of the tumor among the elderly compared with younger patients (27). Several studies claimed that the OS was not associated with the pathological stage in the elderly, and quite a few elderly patients might die of non-cancer-related causes, and thus, complete tumor resection was only a part in improving the prognosis (26,28).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, we could not conclude the favorable surgical approach in the elderly patients regarding long-term survival, which was in line with prior research ( 26 ), and might be attributed to a low malignant behavior of the tumor among the elderly compared with younger patients ( 27 ). Several studies claimed that the OS was not associated with the pathological stage in the elderly, and quite a few elderly patients might die of non-cancer-related causes, and thus, complete tumor resection was only a part in improving the prognosis ( 26 , 28 ).…”
Section: Discussionsupporting
confidence: 72%
“…A propensity-matched study suggested decreased aggressiveness of cIA NSCLC in older patients (>65)noting less N1 or N2 involvement despite the same extent of intraoperative node evaluation (69). However, the impact of worse differentiation and a greater consolidation/tumor ratio (CTR, solid/whole tumor size on lung windows) was far greater-i.e., it may be more important to focus on markers of tumor behavior than age.…”
Section: Sources Of Ambiguity and Nuances Of Applicabilitymentioning
confidence: 99%